Accuracy of Infrared Photodiode Sensors at The Flowrate Measurement in Infusion Device Analyzer with 2 Channel TFT Display - Wafiq Nur Azizah; Triana Rahmawati; Syaifudin Syaifudin (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
The use of infusion is crucial for patient healing. Infusion refers to a fluid that consists of drugs, nutrients, and hydration delivered continuously into the patient's bloodstream over a specific period. One of the types of infusion devices is the infusion pump and syringe pump. These devices play a vital role in accurately and precisely controlling the volume or flow rate of fluids. However, continuous usage of these devices can sometimes result in inaccurate measurements, which can affect their overall accuracy. The accuracy of these devices is crucial for proper dosage administration to patients, particularly in critical situations. Therefore, it is necessary to periodically calibrate healthcare devices, at least once a year, as specified in Ministry of Health Regulation No. 54 of 2015. Calibration is an activity performed to determine the true value of a device. The objective of this study is to develop an Infusion Device Analyzer (IDA) with a TFT LCD display that showcases graphical representations of flow rate parameters. By analyzing the calculation of flow rate values using Infrared Photodiode sensors, the stability of the flow rate graph can be observed on a 7-inch TFT LCD display. The measurement involved the use of two different brands of syringe pumps and two different brands of infusion pumps. The results were presented in real-time on the 7-inch TFT LCD display, both in graphical and numerical formats. Additionally, the data was transmitted via Bluetooth to a PC, allowing the graph to be simultaneously displayed in a Delphi program.The measurement results revealed performance errors when using the Terumo Syringe Pump with Terumo syringes in Channel 1, with values of 0.45% (10 ml/h), 0.72% (50 ml/h), and 0.40% (100 ml/h). In Channel 2, the errors were 0.32% (10 ml/h), 0.40% (50 ml/h), and 0.32% (100 ml/h). When using the B-Braun Syringe Pump with B-Braun syringes, Channel 1 exhibited errors of 0.45% (10 ml/h), 0.7% (50 ml/h), and 0.85% (100 ml/h), while Channel 2 had errors of 0.8% (10 ml/h), 0.3% (50 ml/h), and 1% (100 ml/h). In the case of the Terumo Infusion Pump with Terumo Infusion Sets, Channel 1 showed errors of 0.4% (10 ml/h), 0.5% (50 ml/h), and 0.45% (100 ml/h), and Channel 2 exhibited errors of 0.32% (10 ml/h), 0.4% (50 ml/h), and 0.72% (100 ml/h). Lastly, when using the B-Braun Infusion Pump with B-Braun Infusion Sets, Channel 1 had errors of 0.72% (10 ml/h), 1% (50 ml/h), and 1,2% (100 ml/h), while Channel 2 displayed errors of 0.8% (10 ml/h), 0.72% (50 ml/h), and 0,4% (100 ml/h).INDEX TERMS Infrared Photodiode Sensor, Calibration, Real Time, Flow Rate.